EVALUATION OF THE SENSORY CHARACTERISTICS OF A FRESH CHEESE WITH MICROENCAPSULATED PARACHLORELLA KESSLERI MICROALGAE OIL (@limentech, Ciencia y Tecnología Alimentaria, 2024)
The main objective of this research was the integral evaluation of a milk matrix enriched with microencapsulated oil extracted from the microalgae Parachlorella kessleri. Three specific objectives were established to address different aspects of the project. First, it focused on the formulation and standardization of the milk matrix with the addition of microencapsulated Parachlorella kessleri oil. Through an experimental approach, it was possible to establish an optimal formulation (i.e., high microencapsulated and low salt values) and the manufacturing conditions necessary to produce fresh cheese enriched with this microencapsulated oil, involving the manipulation of key production variables. Subsequently, the evaluation of the nutritional and physicochemical characteristics of the resulting product was focused on. Parameters such as moisture, total solids, pH, and fatty acid profile were analyzed to better understand the nutritional composition of the fresh cheese with the addition of the microencapsulated oil, highlighting its contribution to essential fatty acids, such as omega 3. The last aspect of this research was the sensory evaluation of the fortified fresh cheese. Through sensory analysis, the flavor, texture, and odor attributes of the final product were evaluated, providing an accurate understanding of the sensory perception by consumers, which is essential to evaluate its acceptance in the market. This paper will present the results of the sensory evaluation that supported the feasibility of the inclusion of microencapsulated Parachlorella kessleri oil in the dairy matrix. The enriched fresh cheese maintained organoleptic characteristics similar to those of a traditional fresh cheese, suggesting its potential as an attractive and healthy option for consumers in search of innovative and nutritious dairy products.
Keywords: N-3 fatty acids; Functional food; Food matrix; Microalgae; Microencapsulation